Destination images: antecedents of city marketing, tourism event, and social media marketing concept - Aisah Asnawi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
Building tourism is long-term work. Many elements are involved, and their effectiveness cannot be calculated partially. At present, competition between cities/districts continues to increase, especially in city/district marketing that is tourist-friendly, iconic tourism events, and massive social media marketing. The strong destination image will impact on increasing the number of visits. This research aims to analyze the impact of city/district marketing power, tourist events, and social media on the image of tourist destinations in Maluku. The methodology in this research is based on quantitative analysis using Structural Equation Modelling (SEM) to discuss theory and see the relationship between city/district marketing variables, tourism events, social marketing media, and destination image. This study indicates that city/district marketing has a greater increase in strengthening the image of destinations compared to tourism events and social media marketing. This shows an effective strategy from the government in advancing tourism faster and more robust in increasing the image of a destination.